Lewis Carroll's photography and modern childhood - Waggoner, Diane ca. 21. Jh (Princeton University Press, 2020)
Pictures and conversations : photographic meaning -- Liddell girls : Alice and her sisters -- Pretty boys and little men : becoming a boy -- Theatrical transformations : fancy dress -- In fairyland : partial dress and the nude
Includes bibliographical references and index
Keywords: Carroll, Lewis -- 1832-1898; Porträtfotografie; Carroll, Lewis / 1832-1898; Photography of children / Great Britain / History / 19th century; Children / Great Britain / History / 19th century; Photography, Artistic / History; Photographers / Great Britain / Biography